Rethinking holistic sustainable growth of Malaysian SMEs: a university helix-quadruple bottom line perspective - Islam, Ariful; Abd Wahab, Sazali; Tehseen, Shehnaz (Emerald Publishing, 2024)
Purpose: Malaysian small and medium-sized enterprises (SMEs) are critical for economic development and meeting the sustainable development goals (SDGs); however, many struggle to survive in the long term. So, this study aims to present a model for sustainable growth that bridges the gap between desired growth and managerial competencies. By configuring university helix-induced crowdfunding and opportunity recognition competencies with industry helix-driven innovation, the study encourages a quadruple bottom line (QBL) strategy, helping SMEs attain competitiveness for sustainable growth. Design/methodology/approach: This pilot study used a sequential mixed methods design and adhered to the pragmatic research paradigm. A survey of 52 SCORE-listed manufacturers yielded quantitative data, complemented by qualitative interviews with 7 SME decision makers. This study used NVivo 10 and SmartPLS 4.0 for the necessary analysis. In addition, an effective triangulation strategy has been implemented to explain causation among selected variables. Findings: The findings show that opportunity recognition and crowdfunding are positively associated with SMEs’ ability to grow in a sustainable manner and that exploitative and explorative innovation also mediate those relationships. The qualitative part highlighted key insights for successfully applying this model in Malaysian SMEs. The interview results also suggest that corporate spirituality might help SMEs adopt sustainability-focused practices. Research limitations/implications: More research is required regarding both the methods and results of this pilot study. Although conducting a pilot study increases the likelihood of success in the main study, it does not ensure it. Practical implications: This study equips Malaysian SMEs with a roadmap for achieving sustainable growth. The obtained findings indicate that Malaysian SMEs that develop strong crowdfunding and opportunity recognition competencies are more likely to achieve innovation-focused long-term survival. In addition, incorporating corporate spirituality can enhance their economic, social and environmental performance. Social implications: By supporting more innovation in SMEs, which can improve sustainability-oriented successes and support a healthy economic system, these findings may have a beneficial social change impact. The concept may also act as the foundation for SMEs’ promotion of the SDGs. Originality/value: The study uniquely offers a holistic growth model for Malaysian SMEs founded on the helix-QBL understanding that explains a firm’s sustainability-focused competitive advantage.